Correction: Impact of changes in bond structure on ovonic threshold switching behaviour in GeSe2. Issue 2 (6th January 2021) - Keukelier, Jonas; Opsomer, Karl; Nuytten, Thomas; Sergeant, Stefanie; Devulder, Wouter; Clima, Sergiu; Goux, Ludovic; Kar, Gouri Sankar; Detavernier, Christophe
Abstract : Correction for 'Impact of changes in bond structure on ovonic threshold switching behaviour in GeSe2 ' by Jonas Keukelier et al., J. Mater. Chem. C, 2021, DOI: ; 10.1039/d0tc04086j .